EFEITO DE DIFERENTES PROTOCOLOS DE APLICAÇÃO DE ADESIVOS UNIVERSAIS NAS PROPRIEDADES E LONGEVIDADE DA UNIÃO À DENTINA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
The aim of the present study was to make an in vitro evaluation of the properties and stability of the bond to dentin of new universal adhesive systems applied according to the etch-and-rinse (ER) and self-etching (SE) adhesive strategies. The specific objectives for each of the three studies were: To evaluate the microtensile bond strength (RU), nanoleakage (NI) and degree of conversion (DC) in the time intervals of 24 h (Experiment 1) and six months (Experiment 2) of the universal adhesive systems applied in accordance with the manufacturers’ recommendations for strategies ER and SE; and the effect of an additional hydrophobic layer (Experiment 3, in the immediate time interval) on these same properties. The occlusal surfaces of 140 third molars were flattened until dentin was obtained, and then the teeth were randomly allocated to 28 groups (n=5). In Experiments 1 and 2, 40 teeth were divided into eight groups according to the adhesive used (Peak Universal [Pk], Scotchbond Universal [Sc], Allbond Universal [Al]) and adhesive strategy (ER and SE), with the ER adhesive system Adper Single Bond 2 (SB) and self-etching Clearfil SE Bond (CSE) used as controls. For Experiment 3, 60 teeth were divided into 12 groups according to the adhesive (Sc, Al, G-Bond Plus [Gbp]), adhesive strategy (ER and SE) and with or without hydrophobic layer (Heliobond, HE). After application of the variables adhesives and restorative procedure, the teeth were stored in distilled water (37oC/24 h) and cut to obtain dentin-resin sticks (0.8 mm2 cross-section) which were submitted to the RU and NI tests in the following time intervals: immediate (Experiments 1 and 3) and six months (Experiment 2); and analysis of DC in the immediate time interval. The data of Experiment 1 were submitted to one-way analysis of variance (Adhesive Strategy) and those of Experiments 2 and 3, to twoway analysis of variance (Adhesive strategy vs. Time intervals; and Adhesive strategy vs. Hydrophobic layer) respectively. The analyses were complemented by the Tukey Test (α=0.05). The RU results obtained in Experiment 1 demonstrated that only PkEr and PkSe were similar to the respective control groups (p>0.05); that the other universal materials resulted in lower RU means than those of their controls ER and SE (p<0.05) and that AlSe presented the lowest mean RU values (p<0.05). For NI, the Groups ScEr, ScSe, AlSe, and AlEr presented low levels of NI similar to those of the control groups (p<0.05). For DC, only Group ScSe demonstrated low DC when compared with the other materials (p<0.05). According to the results of Experiment 2, the systems Pk and AlEr presented a reduction in RU (p<0.05) and only Pk underwent significant degradation (NI) after six months (p<0.05). According to Experiment 3, Al and Gbp obtained higher RU results with the ER strategy (p<0.05); the use of HE increased the RU only in strategy SE (p<0.05); a low level of NI was observed only in Groups Sc and Al with the CON+HE strategy and in Group Gbp with SE+HE; Groups Sc and Gbp presented a high DC when used with the ER strategy, which was increased with the application of HE (p<0.05). The DC if Al was similar under all the conditions. From the three experiments of which this study was composed, it could be concluded that: 1) the universal adhesives presented a 13 material-dependent behavior in both strategies (ER and SE) and were inferior, in at least one of the properties evaluated (RU, Nl or DC), when compared with the control adhesives (CSE and SB); 2) In general, after six months the adhesives SE maintained the most stable RU and NI values, which appears to be related mainly to their capacity to form a chemical bond to dental substrate; 3) The use of a hydrophobic layer in strategy SE was able to increase the RU and DC of universal adhesives and the reduction in NI was more dependent on the composition of the adhesive than on the adhesive strategy.
Effect of different universal adhesive application protocols on the properties and longevity of bond to dentin
Keywords: dentina; sistemas adesivos; adesivos convencionais; adesivos autocondicionantes; resistência de união; grau de conversão; nanoinfiltração; dentin; adhesive systems; etch-and-rinse; self-etch; bond strength; degree of conversion; nanoleakage; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA